Comparative description and taxonomy of new hominin juvenile mandibles from the Pliocene of Woranso-Mille (Central Afar, Ethiopia). Issue 132 (July 2019) - Haile-Selassie, Yohannes; Ryan, Timothy M.
Abstract: Mandibular morphology of Australopithecus afarensis is well known based on abundant fossil mandibles of adult individuals from multiple sites in Ethiopia (Hadar, Woranso-Mille, and Middle Awash) and Tanzania (Laetoli). However, there are only a few juvenile mandibles of the species known from these sites. Here, we describe two recently discovered Pliocene hominin juvenile mandibles from Woranso-Mille (KSD-VP-1/29 and MKM-VP-1/626), that have been radioisotopically dated to 3.6 million years ago. We assign these mandibles to Australopithecus afarensis based on their possession of mandibular morphological features considered as distinctive of the species. These specimens not only increase the sample size of juvenile mandibles of A. afarensis from poorly known time period, but also add new information on the degree of variability in juvenile mandibular morphology within the species. Their dentition samples the whole spectrum of size and shape variation in A. afarensis . Our analysis further indicates that symphyseal morphology of the Laetoli mandibles of early A. afarensis falls within the range of variation of mandibles of the species from Hadar, Woranso-Mille, and Middle Awash. Moreover, the fact that the new 3.6 million-year-old juvenile mandibles from Woranso-Mille have a more receeding symphysis than any of the juvenile and most adult mandibles of A. afarensis from the younger Hadar sequence lends support to the observed trend in symphyseal morphological change in the A. anamensis–A. afarensis chronospecies lineage.